Delta beta-thalassaemia in southern Italy: evidence for a single mutational event. Issue 2 (April 1984) - Carè, A; Sposi, N M; Giampaolo, A; Improta, T; Calandrini, M; Petrini, M; Marinucci, M; Tagarelli, A; Brancati, C
Abstract : Haematological and molecular studies on 32 heterozygotes for G gamma A gamma delta beta(0)-thalassaemia from 15 unrelated families from southern Italy are reported. The haematological features of G gamma A gamma delta beta(0)-thalassaemia carriers are compared with those of beta-thalassaemia and Hb Lepore heterozygotes. Striking similarity exists between the phenotypic expression of beta-thalassaemia and Lepore mutations. Globin gene mapping studies indicated that the molecular lesion underlying delta beta-thalassaemia is a large deletion starting from the large intervening sequence of the delta gene and extending downstream from the beta gene. The possibility that delta beta-thalassaemia haplotypes in southern Italy originated from a single mutational event is discussed.